Gender and Regional Differences in Sleep Quality and Insomnia: A General Population-based Study in Hunan Province of China - Tang, Jinsong; Liao, Yanhui; Kelly, Brian C.; Xie, Liqin; Xiang, Yu-Tao; Qi, Chang; Pan, Chen; Hao, Wei; Liu, Tieqiao; Zhang, Fengyu; Chen, Xiaogang (Scientific reports, 2017)
Insomnia and the inability to sleep affect people’s health and well-being. However, its systematic estimates of prevalence and distribution in the general population in China are still lacking. A population-based cluster sampling survey was conducted in the rural and urban areas of Hunan, China. Subjects ( n = 26,851) were sampled from the general population, with a follow-up using the Pittsburgh Sleep Quality Index (PSQI) for interview to assess quality of sleep and Insomnia (PSQI score >5). While the overall prevalence of insomnia was 26.6%, and little difference was found between males (26.3%) and females (27.0%); the mean PSQI score was 4.26 (±2.67), and significant higher in females (4.32 ± 2.70) than males (4.21 ± 2.64, p = 0.003). Individuals in the rural areas tended to report a higher PSQI score (4.45 ± 2.81) than urban residents did (4.18 ± 2.60) (p < 0.001) and the estimates of prevalence of insomnia was 29.4% in the rural areas, significant higher than 25.5% in the urban areas (p < 0.001). Multiple logistic regression analysis showed that female gender, older age, higher level of education, being unmarried, living in the rural area, cigarette smoking and alcohol drinking were associated with insomnia. Our study may provide important information for general and mental health research.